A high performance catalyst of shape-specific ruthenium nanoparticles for production of primary amines by reductive amination of carbonyl compounds. Issue 27 (25th June 2018) - Chandra, Debraj; Inoue, Yasunori; Sasase, Masato; Kitano, Masaaki; Bhaumik, Asim; Kamata, Keigo; Hosono, Hideo; Hara, Michikazu
Abstract : The creation of metal catalysts with highly active surfaces is pivotal to meeting the strong economic demand of the chemical industry. Abstract : The creation of metal catalysts with highly active surfaces is pivotal to meeting the strong economic demand of the chemical industry. Specific flat-shaped pristine fcc ruthenium nanoparticles having a large fraction of atomically active {111} facets exposed on their flat surfaces have been developed that act as a highly selective and reusable heterogeneous catalyst for the production of various primary amines at exceedingly high reaction rates by the low temperature reductive amination of carbonyl compounds. The high performance of the catalyst is attributed to the large fraction of metallic Ru serving as active sites with weak electron donating ability that prevail on the surface exposed {111} facets of flat-shaped fcc Ru nanoparticles. This catalyst exhibits a highest turnover frequency (TOF) of ca. 1850 h −1 for a model reductive amination of biomass derived furfural to furfurylamine and provides a reaction rate approximately six times higher than that of an efficient and selective support catalyst of Ru-deposited Nb2 O5 (TOF: ca. 310 h −1 ).